PERENCANAAN INDIVIDUAL BIMBINGAN DAN KONSELING KOMPREHENSIF KELAS VII SMPN 3 SUNGAI AMBAWANG KUBU RAYA - Deana, Miranda Putri; Yuline, Yuline; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractIndividual planning guidance and counseling is an assistance service to students. Which can be done individually or in groups to foster students' independence in the development of personal life, social life, learning skills and career planning. In the implementation of individual planning comprehensive guidance and counseling includes personal-social individual planning, individual learning planning and individual career planning. As well as the inhibiting factors in carrying out individual planning services and the efforts made in overcoming obstacles. Therefore, researchers want to know the implementation of individual planning comprehensive guidance and counseling. The research problem is